Effect of the Early Application of Evolocumab on Blood Lipid Profile and Cardiovascular Prognosis in Patients with Extremely High-Risk Acute Coronary Syndrome - Li, Jian; Yang, Yu-lin; Wang, Yong-chao; Hao, Yan (International Heart Journal, 2022)
Proprotein convertase subtilisin/kexin 9 (PCSK9) inhibitors significantly reduce low-density lipoprotein cholesterol (LDL-C) and improve the prognosis of patients with acute coronary syndrome (ACS). However, the feasibility and safety of early application of PCSK9 inhibitors on the basis of statins combined with ezetimibe to strengthen lipid lowering in extremely high-risk coronary heart disease populations are still unknown.This study was a prospective, randomized controlled study. A total of 136 patients with extremely high-risk ACS with LDL-C ≥ 3.0 mmol/L after percutaneous coronary intervention (PCI) treatment were randomly assigned 1:1 to the control group (atorvastatin 40 mg/day and ezetimibe 10 mg/day) or the evolocumab group (evolocumab 140 mg every 2 weeks combined with atorvastatin 40 mg/day and ezetimibe 10 mg/day). We compared the blood lipid profiles, major adverse cardiovascular events (MACEs), and adverse reactions. MACEs included cardiogenic death, nonfatal myocardial infarction, nonfatal stroke, and readmission due to angina. Adverse reactions included allergies, myalgia, poor blood glucose control, and liver damage.Within 1 month, the average level of LDL-C in the evolocumab group decreased from 3.54 to 0.57 mmol/L and that in the control group decreased from 3.52 to 1.26 mmol/L. The LDL-C compliance (< 1.0 mmol/L) rate was significantly increased in the evolocumab group compared with the control group (82.35% versus 22.06%, P < 0.01). The average level of lipoprotein (a) (Lp (a) ) in the control group increased by 9.94 ± 51.93% from baseline after treatment, but evolocumab reduced the Lp (a) level (−38.84 ± 32.40%). Additionally, evolocumab further reduced the levels of apolipoprotein B/A1 (−70.56 ± 22.38% versus −51.29 ± 18.14%), cholesterol (−54.76 ± 18.10% versus −41.16 ± 18.14%), and apolipoprotein B (−66.47 ± 26.89% versus −46.78 ± 24.12%) compared with those in the control group, all P < 0.01. The blood lipid levels of both control and evolocumab groups stabilized after 1 month. During the 3-month follow-up, the incidence of MACEs after PCI was lower in the evolocumab group than in the control group (8.82% versus 24.59%, P = 0.015), and evolocumab combined with statins and ezetimibe did not increase the occurrence of adverse reactions (13.24% versus 11.48%, P = 0.762).In patients with extremely high-risk ACS with high levels of LDL-C, adding evolocumab to their treatment regimen as early as possible may enhance lipid lowering, increase the patient's LDL-C compliance rate in the short term, and improve cardiovascular prognosis but will not increase adverse reactions.